2016
DOI: 10.1519/jsc.0000000000001295
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis After Performing Blood Flow Restriction Training: A Case Report

Abstract: Tabata, S, Suzuki, Y, Azuma, K, and Matsumoto, H. Rhabdomyolysis after performing blood flow restriction training: a case report. J Strength Cond Res 30(7): 2064-2068, 2016-Rhabdomyolysis is a serious and potentially life-threatening condition related to resistance training. Despite numerous reports of low-intensity blood flow restriction (BFR) training inducing muscle hypertrophy and increasing strength, few reports of rhabdomyolysis related to BFR training have been published. Here, we report a 30-year-old o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 26 publications
1
44
0
1
Order By: Relevance
“…This is a large response and in contrast to recent evidence (Loenneke, Thiebaud & Abe 2014) however, this is a transient response to unaccustomed exercise and usually subsides within 24 to 72 h (Umbel et al 2009, Wernbom et al 2012 or following repeated exercise (Sieljacks et al 2016). With that said, despite the low response, 3% of practitioners reported rhabdomyolysis in their clients/patients following BFR training which is in line with previous research (Nakijima et al 2006, Iversen, Rostad 2010, Tabata et al 2016), but higher than that reported in physically active military recruits (Alpers & Jones, 2010). It should also be noted that we did not determine how rhabdomyolysis was assessed, but do suggest practitioners exercise caution and screen participants prior to BFR training.…”
Section: Safetysupporting
confidence: 84%
See 1 more Smart Citation
“…This is a large response and in contrast to recent evidence (Loenneke, Thiebaud & Abe 2014) however, this is a transient response to unaccustomed exercise and usually subsides within 24 to 72 h (Umbel et al 2009, Wernbom et al 2012 or following repeated exercise (Sieljacks et al 2016). With that said, despite the low response, 3% of practitioners reported rhabdomyolysis in their clients/patients following BFR training which is in line with previous research (Nakijima et al 2006, Iversen, Rostad 2010, Tabata et al 2016), but higher than that reported in physically active military recruits (Alpers & Jones, 2010). It should also be noted that we did not determine how rhabdomyolysis was assessed, but do suggest practitioners exercise caution and screen participants prior to BFR training.…”
Section: Safetysupporting
confidence: 84%
“…In more controlled conditions, 4 weeks of BFR had no negative effects on pulse-wave velocity, anklebrachial index, prothrombin time, nerve conduction, markers of coagulation or fibrinolysis (Clark et al 2011). Whilst the aforementioned studies have not reported negative side effects of BFR training, more recent case studies have reported rhabdomyolysis (Iversen, Rostad 2010, Tabata et al 2016 and retinal occlusion (Ozawa et al 2015). Furthermore, skeletal muscle damage is reported following BFR training (Umbel et al 2009, Wernbom et al 2012 however, this has been disputed in the literature (Loenneke, Thiebaud & Abe 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This means that the KAATSU training by proper training leaders and instructors can achieve beneficial effects without serious side effects. On the other hand, a recent study (Tabata et al, 2016) reported a risk of rhabdomyolysis by the KAATSU training, however there was no detailed description on the KAATSU training method; it reported that the rhabdomyolysis occurred as a result of KAATSU training with a training instructor. Therefore, the KAATSU training leaders and instructors should maintain / improve their knowledge and skills by participating in academic conferences and reading scientific papers on the KAATSU training.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, cases of rhabdomyolosis have emerged73 74 despite a reported incidence of 0.008% in the aforementioned study. Most recently, this was reported in an obese Japanese male  after only three sets of 20 reps of BFR exercise;74 however, no information regarding the exercise load or occlusive pressure was available, and the individual had been sedentary for a number of years. It is more likely that the cause was the stress of unaccustomed exercise on a sedentary body or the inappropriate use of BFR.…”
Section: Discussionmentioning
confidence: 99%